MENITI SINKRETISME TEKS TANTU PANGGĚLARAN - Turita Indah Setyani (Jurnal Kawistara, 2011)
Tantu Panggělaran (TP) is a work of literature that contains knowledge necessary for human beings to achieve perfection of living which is influenced by Javanese, Hindu (Shivaist), and Buddhist concepts. This research studies syncretism in the text of TP by using the theory of normative multiculturalism. The purpose of this research is to find out how syncretism occurred in people’s lives, as recorded in the text of TP. It is hoped this research can benefit the development of Javanese culture in general, and particularly Old Javanese culture from the late Majapahit era. The results show that TP is the implementation of cultural syncretism of Javanese, Hindu (Shivaist), and Buddhist cultures in a positive, mutualistic relationship.